The Influence Of Profitability On Stock Return With Inflation As A Moderating Variable - Paulus Sugito; Irvan Noormansyah; Nursanita Nasution (BPJP - STEI, 2018)
Abstract—This study aims to analyze the effect of profitability on stock returns with inflation as a moderating variable. The variables tested in this research are profitability proxy for Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM), inflation and stock returns. The sample of this research uses 12 automotive companies and automotive components that consistently published financial statements in the Indonesia Stock Exchange period 2013-2017. Samples were taken by purposive sampling method which is a method of samples based on certain criteria. These variables analyzed using panel data regression. In this study, testing hypotheses used the t test, F test and regression used Moderated Regression Analysis (MRA). Panel data regression results showed Adjusted R-squared of 0.153836, which means that the magnitude of the influence of the independent variable moderated by inflation on the dependent variable that can be explained by this equation model is 15.38%. While the remaining 84.62% is influenced by other factors not taken into account in this regression model. The conclusions of this research show that ROA has a significant positive effect on stock returns, ROE has a negative effect on stock returns, NPM has no effect on stock returns, ROA moderated by inflation has a negative effect on stock returns, ROE moderated by inflation has a significant positive effect on stock returns, and NPM moderated by inflation does not affect stock returns